How Can Digital Voice Assistant Impact Consumers’ Experience in E-Commerce? - Gu, Yaofei (International Journal of Global Economics and Management, 2025)
Digital Voice Assistant (VA in short) is intelligence software tant responds to voice commands and can run on any device. It enables functions such as chatting, operating devices, task ranging, and controlling smart home appliance. The well-known VA on market include Alexa (Amazon), SIRI (Apple), Google Assistant (Google), XiaoAi (XiaoMi), Tmall Genies (Alibaba), etc. With the development of VA, it eventually becomes an innovate channel in e-commerce, who enables users to accomplish shopping-related missions and uses natural language as an interface. This dissertation aims to study consumers’ user experience while shopping through Voice Assistants. The method to collect data is by questionnaire, therefore achieve a quantitively analysis. This dissertation answers tree research questions in order to further understand the object: 1). VA shopping’s characteristic: How VA shopping differs from traditional e-commerce channels through user-experience? 2) What is the consumers’ attitude for shopping through voice assistant? 3) What is consumers’ attendance on voice assistant as a shopping channel? Regarding the customer journey of VA shopping and traditional ways, there didn’t show a huge difference between them. The most different point between VA shopping and traditional e-commerce shopping channel is that VA uses the natural language as interface while traditional ways using picture-text (visually). So that the information present by VA is less complex and hard to make an intuitive impression of articles as the traditional channels. It consequences that VA relies more on the intelligence of its AI algorithm. As the result of survey, users’ attitude toward experience on VA shopping is rather positive. Most of the users are satisfied with it and are willing to share this channel to others. However, those potential users remine an uncertain attitude. They all agree that as advantages, shopping through VA is more time-saving, easy to operate, and enable users to multi-tasks that frees their hands. But as for disadvantages, the article list is too short to making a compare, it couldn’t make an intuitive impression, and the recommendations are not accurate enough. Potential users also concern the payment security. The market forecast for Voice Assistant shows a steady raising trend, which guarantees the user base for VA shopping. While users show their positive point of views about VA shopping, the future of VA has a large potential of development. Among the respondents' suggestions for improving VA shopping, I summarize their opinions in the following points: 1) Some of AI’s behaviors are very stupid.2) Speech recognition is not accurate enough; keyword capture is not accurate enough. 3) Simplify the purchase process, order confirmation is too cumbersome. 4) Optimize the personalized recommendation system. 5) Improves the privacy in public. 6) Protect user privacy and payment security.7) Added child protection.8) The recommendation system should avoid to be affected by advertising and sponsorship (Ensure the authenticity of the recommendation). This dissertation tends to provide a theoretical help for merchants and stakeholders on developing VA shopping, and hoping to provide a reference for other researchers. After a study of users’ point of view on user experience, I make a several recommendations on VA’s development, marketing strategy and UX design in VA shopping.